Perancangan Sistem Informasi Laundry Pada Beach Laundry Kotapinang Berbasis Web - Sari, Okvita (Journal of Computer Science and Information System(JCoInS), 2021)
The world development in this millennium era is very rapid, especially in the field of information technology. The level of speed and accuracy of information is a very big thing because it must be supported by adequate information technology. Likewise in the laundry business services the computerized system that is applied produces information quickly and precisely. However, based on the survey that has been conducted to date, Beach Laundry does not have its own information system and still uses a manual system, so that the search for data experiences difficulties and requires a long process. This laundry also does not have an accurate database storage system so that all data is still stored in a book. Laundry Information System at Web-based Kotapinang Beach Laundry is made as a solution for Beach Laundry so that this system can provide up-to-date information and facilitate the process of making transaction reports quickly, precisely and accurately, so as to minimize errors that may occur.